Sorption/Desorption of Lincomycin from Three Arid‐Region Soils. Issue 5 (1st September 2013) - Williams, C. F.; Watson, J. E.; Nelson, S. D.; Walker, C. W.
Abstract : The antibiotic lincomycin is commonly found in treated municipal waste water and in waste from swine and poultry production. Environmental disposal of these wastes has the potential to introduce a significant mass of lincomycin into the ecosystem. In the present study, a series of sorption and desorption experiments were conducted to determine the potential mobility of lincomycin in soils from arid environments. Sorption and desorption isotherms were obtained for lincomycin using three different soils. Isotherms were fit to the Freundlich equation. Adsorption of lincomycin was found to have a K f of 11.98 for a biosolid‐treated soil (1.58% OC) and a K f of 210.15 for a similar unamended soil (1.42% OC). It was also found that for a low‐organic‐content soil the K f was 5.09. The differences in adsorption can be related to the soil pH and the pKa of lincomycin (7.5–7.8). When the soil solution pH is below the pKa, the cationic species of lincomycin dominates, resulting in increased water solubility. Interaction with the cation exchange complex is minimal due to a high solution cation concentration (Ca 2+ and Na + ). Desorption isotherms also indicate that when the solution pH is lower than the pKa, retention of lincomycin is reduced. Our results indicate that the mobility of lincomycin in these arid region soils is dependent on soil pH.